Evaluation Of Implementation Strategies And Methods To Improve Efficiency In The Bagong Main Dam Project Trenggalek - moch. khamim; Mohamad Zenurianto; Raden Ajeng Mariyana; Roland Gasenda Suryaningrat (CV. Creative Tugu Pena, 2025)
Earthfill dam construction requires effective strategies to ensure structural safety, construction quality, and efficient use of time and resources. This study examines the construction strategy and implementation method of the Main Dam of the Bagong Dam Project, Indonesia, which is designed as a vertically zoned earthfill embankment with a length of 620 m, a crest width of 12 m, a crest elevation of +330 m, and a height of 82 m. The research focuses on the application of a zoning-based construction approach to improve construction efficiency under complex field condition. The results indicate that dividing the embankment into six functional zones enables systematic layer-by-layer construction and parallel work execution, resulting in a planned construction duration of 937 working days. The integration of material zoning, quality control procedures, and optimized equipment management ensured that all embankment layers achieved more than 95% of maximum dry density. Coordinated equipment utilization further improved productivity, allowing approximately 304,653 m³ of embankment work to be completed within 53 working days during critical construction stages. In addition, the implementation of a structured safety management system supported the achievement of zero-accident construction performance. These findings demonstrate that the integration of zoning strategy, systematic construction sequencing, quality management, equipment planning, and safety control significantly enhances time and cost efficiency while maintaining construction quality. The proposed approach provides a practical framework for earthfill dam construction projects in Indonesia and other regions with similar geological and climatic conditions.